The Effects of Aging Period and Freezing Sequence on Desmin Degradation of Longissimus lumborum, Semitendinosus, and Biceps femoris Steaks - Taylor M. Dieball (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: The objective of this study was to examine the impact of freezing and aging sequence on the degradation of desmin, an indicator of tenderness during post-mortem proteolysis, within three beef muscles across two aging periods. Study Description: Longissimus dorsi, semitendinosus, and biceps femoris steaks were fabricated into 1-in. steaks and assigned to one of four treatment combinations: age- then-freeze (AF) for 21 or 28 days or freeze-then-age (FA) for 21 or 28 days. Samples were ground and frozen and then prepared for Western blotting to evaluate desmin degradation. Desmin bands were visualized, and images were captured to quantify intact and degraded desmin. The Bottom Line: Reversing the freezing order increased desmin degradation for steaks aged for 28 days indicating an increase in proteolytic activity. Previous research indicates there were no differences in instrumental tenderness for this project. Thus, even with increased protein degradation, the change was not enough to affect tenderness.
Keywords: proteolytic; freezing; tenderness